GLOBALIZATION AND INTERNATIONAL RELATIONS - Simeunović, Dragan (Serbian political thought, 2026)
To understand the relation between globalization and international relations, it is necessary to propaedeutically differentiate notions of new world order, globalism, and globalization that are often used without much theoretical understanding, sometimes even as synonyms, which creates terminological confusion. These are three different terms that are related because they refer to intertwined phenomena. Globalism is an ideology, globalization is a process of implementing the ideological premises of globalism, and the new world order is a political- legal system of an emerging world. Concept and practice of globalization include radical change in the modern world in favour of one centre of power and thus imply drastic change in international relations. Globalization implies that contemporary international relations should be characterized by: informal government of the world from one centre of power by controlling and guiding global political, economic, and financial flows; democratization of all world countries by introducing Euro-Atlantic model of democracy as the only valid one; negation of national sovereignty and overcoming national identity; diminished role of the UN and of all international organizations and institutions where proponents of globalizations are not decision makers; ‘managerial’ instead of mediating diplomacy; exclusivity of the right of globalists to use force in international relations; favoring humanitarian interventions as a type of armed conflicts; attempt to direct migrant flows and their intensity; deprivation of rights to progress to all non-globalized countries, even more stronger ones such as Russia and China; putting international relations directly into service of satisfying interests of multinational companies. The proponents of globalization have had only limited success in these efforts due to various types of resistance. Globalization has been mostly achieved at the international economic level, and much less at the international political and international security levels. Although the beginning of globalization announced a fast end to the national state, its sovereignty, and consequently a nation as its basis, this has not happened. Almost everything that has had a national prefix resisted globalization to a greater or lesser extent in the name of the right of the individual to exist as much as the general, and this is the main reason why globalists see the national as the greatest threat. The time of great migrations, as well as the war between Russia and Ukraine, fueled by arms, funds, and logistics of the Western forces, brought new, great, and consequently still unfathomable challenges not only to globalization as a process, but to globalism as an ideology and new world order as a projected political-legal construction of a global system. Russia has announced the new concept of a new world order, and many countries, some of which are EU members, have stood up against global models, thus pivoting strongly towards their national interests, restoration of their national sovereignty, and strengthening of their national values, although it seemed up until recently that these countries had completely merged into supranational unity. It is becoming more obvious that the war and migrations were just a reason for a reiterative renewal of the concept of a national state as an important heritage and its greater independence, and not only on the territory of Europe, indicating a process of re-sovereignisation in globalized areas as a more widespread phenomenon. This, as well as other current processes of using and distributing power among states at a global level, will undoubtedly strongly affect the profiling of international relations in the near future.